Islamic Education Materials Era 4.0 21st Century Perspective Imam Al-Ghazali - Moh. Faizin; Yunita Eka Nur Prastiwi; Fadila Firdaus Umar; Faradilla Zahratun Nisa (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
In general, this research is used to find out how Islamic education material is in the 4.0 era from the perspective of Imam Al-Ghazali. The method used in collecting data in this study is Library Research, which contains written sources from books, articles, or books relevant to this study's discussion. This study discusses the meaning of Islamic education material according to Imam al-Ghazali, the era of revolution 4.0, and the challenges of Islamic education material in the 4.0 era. Al-Ghazaki argues that the material aspects of Islamic education include faith, morals, reason, and social and physical education. These materials have been developed and adapted to the conditions of society in this era. According to Imam Al-Ghazali, there are also two ways to achieve Islamic education material: memorizing and mastering it in stages. Then there is also a conclusion that can be drawn from this research that in this digital era, Islamic education materials are needed to help achieve the desired goals of Islamic education. Keywords: Material; Education; Islam; Al-Ghazali.